Advancing Universal Health Coverage : What Developing Countries Can Learn from the Israeli Experience? - Rosen, Bruce; Waitzberg, Ruth (World Bank, Washington, DC, 2018)
The Israeli health system provides universal coverage of a broad benefits package in a highly efficient manner. At the same time, the Israeli health system faces significant challenges, including lack of universal coverage for long-term care and adult dental care, center-periphery gaps, insufficient care integration, long waiting times for some elective procedures, and a growing private health care sector that poses several threats to the public system, cost containment, and health system equity. The Israeli health care system has benefited greatly from its capacity to identify relevant innovations in other countries and adapt them to Israel. At the same time, the Israeli experience can be a source of lessons for other countries. Aspects of the Israeli system that might be particularly relevant to middle-income countries include health plan competition in a clear and simple institutional environment, the reliance on health plans such as managed care and patient-centered organizations, the emphasis on primary care, and the investment in e-health. The manner in which Israel is grappling with its growing private sector can be a source of strategies middle-income countries could consider, and a source of strategies they should avoid.